Accuracy evaluation of the semi-automatic 3D modeling for historical building information models. Issue 5 (4th July 2018) - Antón, Daniel; Medjdoub, Benachir; Shrahily, Raid; Moyano, Juan
ABSTRACT: It is stated that 3D recording and modeling of heritage buildings entail accurate building models (as-built). However, this paper presents an analysis of the 3D modeling accuracy for the creation of historical building information models (HBIM), considering the complexity and the deformations of historical buildings, using point cloud data and BIM tools. The 3D modeling processes analyzed are based on a three-stage semi-automatic approach leading to the generation of HBIM, including manual and automatic processes. The three stages consist of: (a) optical and terrestrial laser scanning; (b) meshing processes; and finally (c) 3D solid modeling to be assembled into HBIM. Next, this approach analyzed the mesh deformations generated automatically in comparison to the initial point cloud data. The deformations and the accuracy evaluation have been undertaken using different commercial software. Finally, our modeling approach shows that it can improve the accuracy of the 3D models achieved using existing BIM technologies.